How to Avoid a Pension Crisis: A Question of Intelligent System Design - Alessandro Cigno (Institute for the Study of Labor (IZA), 2009)
Conventional pension systems suffer from a design defect which makes them financially unsustainable, and a source of inefficiency for the economy as a whole. The paper outlines a second-best policy which includes a public pension system made up of two parallel schemes, a Bismarckian one allowing individuals to qualify for a pension by working and paying contributions in the usual way, and an unconventional one allowing them to qualify for a pension by having children, and investing time and money in their upbringing.
Keywords: D13; D64; H55; J13; J14; J26; 330; pension reform; implicit pension taxes and subsidies; child benefits; fertility; labour productivity; Gesetzliche Rentenversicherung; Rentenreform; Second Best; Umlageverfahren; Familienleistungsausgleich; Arbeitsproduktivität; Fertilität; Theorie; Deutschland